ISLAMIC BANKING PERFORMANCE BASED ON BANK HEALTH BEFORE AND DURING THE COVID-19 - Suryani Sri Lestari; Siti Hasanah; Saniman Widodo; Mustika Widowati; Mella Katrinasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The research entitled "Sharia Banking Performance Based on Bank Health Before and During the Covid-19 Pandemic" was based on the Covid-19 pandemic that hit Indonesia, which had an impact on bank health but also hampered Indonesia's economic growth. One of the sectors that the government has focused on in dealing with economic problems is banking, which is predicted to be affected by the pandemic. The purpose of this study is to analyze the impact of the Covid-19 pandemic on the performance of Islamic banking using the health ratio variables of Islamic banks, namely: Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Return on Assets (ROA), Operational Income Operational Costs (BOPO), and Capital Adequacy Ratio (CAR). This study uses secondary data, namely quarterly financial reports for the two years before (2018-2019) and the two years during the Covid-19 pandemic (2020-2021). The sample used in this study is Islamic Commercial Banks that fall into the BUKU 2 category (Business Commercial Banks), namely Banks with Core Capital of at least IDR 1,000,000,000,000.00 (one trillion rupiah) to less than IDR 5,000,000. 000,000.00 (five trillion rupiah), including Bank Muamalat Indonesia, BCA Syariah Bank, Bank Panin Dubai Syariah, Bank Mega Syariah, and Bank Aceh Syariah. Data testing method using descriptive statistics, normality test, and hypothesis testing. For the normality test use the Shapiro-Wilk test due to the small number of samples. Hypothesis testing used the Paired Sample T-Test for normally distributed data and the Wilcoxon Signed Rank Test for abnormally distributed data through the SPSS 25 program with a significance level of